2015
DOI: 10.1007/s13679-015-0172-9
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Dysbiosis in Obesity-Linked Metabolic Diseases and Prebiotic Potential of Polyphenol-Rich Extracts

Abstract: Trillions of microorganisms inhabit the human body, strongly colonizing the gastro-intestinal tract and outnumbering our own cells. High-throughput sequencing techniques and new bioinformatic tools have enabled scientists to extend our knowledge on the relationship between the gut microbiota and host's physiology. Disruption of the ecological equilibrium in the gut (i.e., dysbiosis) has been associated with several pathological processes, including obesity and its related comorbidities, with diet being a stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
112
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(122 citation statements)
references
References 98 publications
1
112
0
1
Order By: Relevance
“…Collectively, these studies reveal that polyphenols act as prebiotic supplements that can positively modulate gut microbiota composition mainly through the enrichment of beneficial bacteria and the inhibition of pathogenic bacterial growth (Anhe et al, 2015b; Le Barz et al, 2015; Fändriks, 2017). …”
Section: Therapeutic Modulation Of Gut Microbiota To Restore Lipid Anmentioning
confidence: 99%
“…Collectively, these studies reveal that polyphenols act as prebiotic supplements that can positively modulate gut microbiota composition mainly through the enrichment of beneficial bacteria and the inhibition of pathogenic bacterial growth (Anhe et al, 2015b; Le Barz et al, 2015; Fändriks, 2017). …”
Section: Therapeutic Modulation Of Gut Microbiota To Restore Lipid Anmentioning
confidence: 99%
“…Additionally, obese people usually exhibit a lower bacterial diversity and gene richness compared to healthy ones . Although the bacterial profile of the obesity is still not well‐known, it has been reported that obesity affects gut microbial ecology and dysbiosis of gut microbiota contributes to obesity . Thus, the goal of obesity prevention and treatment might be achieved by intentionally manipulating gut microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence suggests that in conjunction with the long-known defects in hormonal and inflammatory states, obesity and T2D are also characterized by dysbiosis(2, 3). Once thought to be simple parasitic passengers, we are now aware of the complex regulatory role that gut microbiota play in our digestion, immune response, metabolism, and even mental status(4, 5).…”
Section: Introductionmentioning
confidence: 99%